A Review of the “Open” and “Closed” Circulatory Systems: New Terminology for Complex Invertebrate Circulatory Systems in Light of Current Findings - Reiber, Carl L.; McGaw, Iain J. (International Journal of Zoology, 2009)
Invertebrate cardiovascular systems have historically been viewed as sluggish, poorly regulated, and “open”, where blood bathes the tissues directly as it moves through a system of ill-defined sinuses and/or lacunae without an endothelial boundary. When examining cardiovascular/circulatory morphology and physiology in a broader evolutionary context, one can question the very nature of the definition of a “closed” versus “open” circulatory system. Viewed in this context a number of invertebrates have evolved incomplete or even completely cell-lined vessels and or lacunae with a highly branched vasculature that allows for the production of significant driving pressures and flows to meet relatively high metabolic demands driven by active life styles. In light of our current understanding of invertebrate cardiovascular systems and their paralleled complexity to vertebrate systems, a number of long established paradigms must be questioned and new definitions presented to better align our understanding of the nature of “open” versus “closed” cardiovascular systems.